Exploring the Role of Posttranslational Modifications in Spinal and Bulbar Muscular Atrophy - Gogia, Neha; Ni, Luhan; Olmos, Victor; Haidery, Fatema; Luttik, Kimberly; Lim, Janghoo (Frontiers in Molecular Neuroscience, 2022)
Spinal and Bulbar Muscular Atrophy (SBMA) is an X-linked adult-onset progressive neuromuscular disease that affects the spinal and bulbar motor neurons and skeletal muscles. SBMA is caused by expansion of polymorphic CAG trinucleotide repeats in the Androgen Receptor (AR) gene, resulting in expanded glutamine tract in the AR protein. Polyglutamine expansion renders the mutant AR protein toxic, resulting in the formation of mutant protein aggregates and cell death. This classifies SBMA as one of the nine known polyglutamine diseases. Like other polyglutamine disorders, the expansion of the polyglutamine tract in the AR protein is the main genetic cause of the disease; however, multiple other mechanisms besides the polyglutamine tract expansion also contribute to the SBMA disease pathophysiology. Posttranslational modifications (PTMs), including phosphorylation, acetylation, methylation, ubiquitination, and SUMOylation, are a category of mechanisms by which the functionality of AR has been found to be significantly modulated and can alter the neurotoxicity of SBMA. This review summarizes the different PTMs and their effects in regulating the AR function and discusses their pathogenic or protective roles in context of SBMA. This review also includes the therapeutic approaches that target the PTMs of AR in an effort to reduce the mutant AR-mediated toxicity in SBMA.